PP black non-heat-absorption composite material applied to automobile central control interior trim parts and preparation method
By adding components such as polypropylene composite materials, components such as dioxide-Elot Stone dual network gas gel, the polypropylene composite material has been solved in the aspects of low temperature resistance, size stability, thermal heat resistance and other aspects. The mechanical properties and flame retardant performance of materials are significantly improved, and it is suitable for the interior of the car control.
Patent Information
- Application Number
- CN202411705658.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-24
AI Technical Summary
Polypropylene composites have poor low temperature impact resistance, dimensional stability, heat stability, etc., which limits their application in the field of automotive central control interiors.
Polypropylene resin, ethylene butylene copolymer, polyethylene resin, carbon fiber, carbon black and zirconium dioxide-halloysite double network aerogel are blended to improve the thermal insulation performance of the material through the structure of the aerogel. , and improve the mechanical properties and flame retardancy of the material through carbon fiber and flame retardants.
It significantly improves the low temperature impact resistance, size stability, thermal resistance and flame retardant performance of polypropylene composite materials, making it more suitable for the interior of the car.
Smart Images

Figure P2DRCIYKG6IVPLL8I5WTXQUQ51AOX0NK85FQOS9C
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer composite materials, and in particular to a PP black non-absorbent composite material used for automobile central control interior decoration parts and a preparation method thereof. Background Art
[0002] Polypropylene resin (PP) has high crystallinity and regular structure, so it has excellent mechanical properties. At the same time, polypropylene resin has been widely used in the field of automotive central control interiors due to its light weight, heat resistance, and easy processing.
[0003] Patent CN103467855B discloses a black filled polypropylene composite material and its preparation method and application. The black filled polypropylene composite material contains the following components by mass fraction: polypropylene 47-98.8%; filler 0-40%; elastomer 0-10%; primary antioxidant 0.2-0.8%; secondary antioxidant 0.2-0.8%; carbon black 0.4-1.0%; processing aid 0.4%. Carbon black refers to furnace carbon black with an iodine absorption value of 45-145 mg / g. The present invention reduces the adverse effect of furnace carbon black with a suitable iodine absorption value on the heat-oxidative aging resistance of polypropylene materials by adding furnace carbon black with a suitable iodine absorption value, reduces the antioxidant content in the polypropylene material, and improves the heat-oxidative aging resistance of the black filled polypropylene material; while improving the heat-oxidative aging resistance, maintaining good dispersibility and coloring, the amount of antioxidant is reduced, thereby reducing product costs.
[0004] Patent CN112011123B discloses a low heat storage polypropylene composite material for automobile interior parts and its preparation method. The invention comprises the following raw materials: 55-75 parts of polypropylene, 5-15 parts of polyolefin elastomer, 10-20 parts of talcum powder, 3-10 parts of infrared reflective filler A, 3-10 parts of infrared reflective filler B, 0.6-1.0 parts of antioxidant, 0.3-0.5 parts of dispersant, 0.5-3 parts of deodorant, 0.3-3 parts of scratch resistant agent, 0.5-2 parts of stabilizer, 1-3 parts of infrared reflective pigment; the invention also provides a preparation method of the polypropylene composite material. The infrared reflective filler A, infrared reflective filler B and infrared reflective pigment of the invention are compatible with polypropylene, have good blending effect, increase the reflection of the polypropylene composite material to visible light, infrared light and ultraviolet light radiation energy, reduce the ability to absorb light radiation energy, reduce the temperature inside the car, and increase the comfort of the passengers.
[0005] Although polypropylene resin (PP) has many excellent properties, it also has some shortcomings, mainly including: poor low-temperature impact resistance, long-term heat stability, dimensional stability and other aspects. The above defects can easily lead to limited application of the material. Summary of the invention
[0006] In view of the needs and deficiencies of the prior art, the present invention discloses a PP black non-absorbent composite material used for automobile central control interior parts and a preparation method thereof. The prepared composite material has good mechanical properties, effectively improves the low-temperature impact resistance and dimensional stability of the polypropylene composite material; and has excellent heat resistance and heat insulation properties, and the flame retardant property also reaches V-0 level.
[0007] In order to solve the technical problem of this application and achieve the above-mentioned purpose, the technical solution provided by the present invention is as follows: A PP black non-absorbent composite material for automobile central control interior parts, comprising the following components in parts by weight: 120-140 parts of polypropylene resin, 20-30 parts of ethylene butene copolymer, 10-20 parts of polyethylene resin, 5-10 parts of carbon fiber, 1-3 parts of carbon black, 10-15 parts of zirconium dioxide-halloysite double network aerogel, 2-4 parts of ammonium polyphosphate, Polypropylene grafted with maleic anhydride 0.2-0.5 parts, 0.5 to 1 part of tri(2,4-di-tert-butylphenyl)phosphite.
[0008] Furthermore, the composite material is composed of the following components in parts by weight: 120-140 parts of polypropylene resin, 20-30 parts of ethylene butene copolymer, 10-20 parts of polyethylene resin, 5-10 parts of carbon fiber, 2-3 parts of carbon black, 10-15 parts of zirconium dioxide-halloysite double network aerogel, 2-4 parts of ammonium polyphosphate, Polypropylene grafted with maleic anhydride 0.2-0.5 parts, 0.5 to 1 part of tri(2,4-di-tert-butylphenyl)phosphite.
[0009] Furthermore, the composite material is composed of the following components in parts by weight: 125-135 parts of polypropylene resin, 24-26 parts of ethylene butene copolymer, 13-17 parts of polyethylene resin, 7-8 parts of carbon fiber, Carbon black 2-2.5 parts, 12-13 parts of zirconium dioxide-halloysite double network aerogel, 3-4 parts of ammonium polyphosphate, Polypropylene grafted with maleic anhydride 0.3-0.4 parts, 0.7 to 0.8 parts of tri(2,4-di-tert-butylphenyl)phosphite.
[0010] Furthermore, the weight average molecular weight of the polypropylene resin is 50,000 to 60,000, and the melt index is 30 to 50 g / 10 min.
[0011] Furthermore, the polyethylene resin is a linear polyethylene resin Furthermore, the length of the carbon fiber is 60 to 90 nm.
[0012] Furthermore, the particle size of the carbon black is 20 to 30 nm.
[0013] Furthermore, the preparation steps of the zirconium dioxide-halloysite double network aerogel are as follows: (1) dissolving 5 parts of polyethylene glycol in 100 parts of water at 80°C and stirring vigorously for 2 hours; dispersing 10 grams of halloysite nanotubes in 100 parts of water at 40°C and stirring for 10 minutes to obtain a uniform suspension. The polyethylene glycol solution and the halloysite nanotube suspension are mixed, then poured into a container and subjected to ultrasonic dispersion treatment for 20 minutes. Then, 0.5 parts of saturated borax solution are added dropwise to the mixture, and the mixture is stirred continuously until it becomes viscous, and then poured into a mold. The mold is placed in a freezer at -20°C for 24 hours and dried in a vacuum freeze dryer for 8 hours to obtain the first halloysite-polyethylene glycol network aerogel; (2) 10 parts of tetra-tert-butoxy zirconium, 20 parts of anhydrous ethanol and 15 parts of water are added to a reaction container, stirred at 40°C for 15 minutes, and then slowly added with a concentration of 0.05 mol·L -1 / hydrochloric acid solution, adjust the pH to 2.6, and continue stirring for 20 min to obtain ZrO 2 Sol. ZrO 2 The sol and the first network aerogel of halloysite-polyethylene glycol are placed in a container in a vacuum environment, and the first network aerogel of halloysite-polyethylene glycol is immersed in ZrO 2 After completely removing the air bubbles in the sol, add ammonia solution to the sol until the pH is 7.2, and stir the solution evenly. After 30 minutes, the sol becomes a wet gel, and then it is immersed in ethanol for aging for 24 hours at room temperature. 2 The supercritical drying tank is used for supercritical drying, and finally the zirconium dioxide-halloysite double network aerogel is obtained.
[0014] The technical idea of this application is to select aerogel to improve the non-absorptive performance of the composite material. The aerogel is composed of nanometer and / or micrometer-scale particles, and there are a large number of gaps between the particles. The air or other gases in the gaps usually have very low thermal conductivity, which gives the aerogel extremely low thermal conductivity; in addition, the network structure in the aerogel provides a complex path and increases the path length of heat transfer, which increases the difficulty of heat transfer, thereby improving the thermal insulation effect. This application is specifically based on halloysite aerogel, and further utilizes the excellent physical properties and thermal insulation properties of zirconium dioxide. The advantages of the two are combined in the form of aerogel to form a double-network aerogel, which better improves the heat resistance and thermal insulation properties of the composite material, so that it has good non-absorptive performance.
[0015] In the present application, ammonium polyphosphate is used as a flame retardant, which can effectively improve the flame retardant properties of the composite material; at the same time, the zirconium dioxide-halloysite double network aerogel can also play a good flame retardant role, and the two synergistically improve the overall flame retardant properties of the composite material.
[0016] The present invention uses polypropylene resin (PP), ethylene-butene copolymer, and polyethylene resin (PE) to blend to form a polymer composite material with improved mechanical properties, which effectively brings into play the advantages of both, improves its mechanical properties, and can make up for the shortcomings of each. The applicant found in the course of research that the synergy of the three can solve the defect of poor dimensional stability of the polypropylene composite material.
[0017] Although blending can improve mechanical properties, the present application further adds a certain amount of carbon fiber, which can also enhance the hardness and impact strength of the polypropylene composite material to a certain extent.
[0018] The present invention uses carbon black as a black colorant to give the polypropylene composite material a high blackness and good high gloss; in addition, carbon black is also the most commonly used conductive additive in polymer composite materials, which improves the conductivity of the material by forming a conductive network, thereby making the polypropylene resin composite material have good antistatic properties. It has obvious advantages for automotive central control interior parts. Furthermore, the particle size of carbon black is 20 to 3 nm, which can be effectively dispersed evenly in the polypropylene composite material.
[0019] A method for preparing a PP black non-absorbent composite material for automobile central control interior parts, comprising the following steps: (1) Weigh the components in the appropriate proportions and set aside; (2) Pour polypropylene resin, zirconium dioxide-halloysite double network aerogel, and carbon black into a stirring device and stir evenly to form material group A; (3) Pour ethylene-butene copolymer, polyethylene resin, carbon fiber, ammonium polyphosphate, and polypropylene grafted maleic anhydride into a stirring device and stir evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.
[0020] Furthermore, the set temperature of the twin-screw extruder is: section one: 180-200°C, section two: 185-205°C, section three: 190-210°C, section four: 195-215°C, section five: 185-205°C, section six: 185-205°C, section seven: 190-200°C, section eight: 195-205°C, section nine: 195-215°C, and die head: 200-210°C.
[0021] Furthermore, the rotation speed of the twin-screw extruder is 300-500 rpm.
[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) With respect to automobile center console interior parts, the present invention provides a polymer composite material formed by blending polypropylene resin (PP), ethylene-butene copolymer, and polyethylene resin (PE). The composite material has good mechanical properties and excellent non-absorption properties, and can solve the defect of poor dimensional stability of polypropylene composite materials.
[0023] (2) The creative use of zirconium dioxide-halloysite double network aerogel as an additive can work synergistically with flame retardants to improve the flame retardancy of composite materials, which can effectively improve safety.
[0024] (3) Carbon black is used to give the composite material a high gloss and high blackness appearance, providing a good overall visual effect for the car's central control. The black color also gives the central control interior parts good antistatic properties. DETAILED DESCRIPTION
[0025] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0026] Main ingredients: Polypropylene resin is Lotte G-153 from Korea. The polyethylene resin is a linear polyethylene resin, Sinopec product M2750, Ethylene butene copolymer is LC175 produced by LG Company of Korea Halloysite nanotubes are products of Zhengzhou Golden Sunshine Ceramics Co., Ltd. The carbon black is high-pigment carbon black from Anyang Daimo New Materials Co., Ltd.
[0027] Preparation of Zirconium Dioxide-Halloysite Double Network Aerogel: The preparation steps of zirconium dioxide-halloysite double network aerogel are as follows: (1) dissolve 5 parts of polyethylene glycol in 100 parts of water at 80°C and stir vigorously for 2 hours; disperse 10 grams of halloysite nanotubes in 100 parts of water at 40°C and stir for 10 minutes to obtain a uniform suspension. Mix the polyethylene glycol solution and the halloysite nanotube suspension, pour them into a container, and disperse them in ultrasound for 20 minutes. Then add 0.5 parts of saturated borax solution to the mixture, stir continuously until it becomes sticky, and then pour it into a mold. Place the mold in a freezer at -20°C for 24 hours and dry it in a vacuum freeze dryer for 8 hours to obtain the first halloysite-polyethylene glycol network aerogel; (2) add 10 parts of tetra-tert-butoxyzirconium, 20 parts of anhydrous ethanol and 15 parts of water to the reaction container, stir at 40°C for 15 minutes, and then slowly add a concentration of 0.01 mol·L -1 / hydrochloric acid solution, adjust the pH to 2.6, and continue stirring for 20 min to obtain ZrO 2 Sol. ZrO 2 The sol and the first network aerogel of halloysite-polyethylene glycol are placed in a container in a vacuum environment, and the first network aerogel of halloysite-polyethylene glycol is immersed in ZrO 2 After completely removing the air bubbles in the sol, add ammonia solution to the sol until the pH is 7.2, and stir the solution evenly. After 30 minutes, the sol becomes a wet gel, and then it is immersed in ethanol for 24 hours at room temperature. 2 The supercritical drying tank is used for supercritical drying, and finally the zirconium dioxide-halloysite double network aerogel is obtained.
[0028] Unless otherwise specified, the aerogels used in the following examples and comparative examples are prepared as described above.
[0029] A PP black non-absorbent composite material for automobile central control interior parts, comprising the following components in parts by weight: 120 parts of polypropylene resin, 20 parts of ethylene butene copolymer, 10 parts of polyethylene resin, 5 parts of carbon fiber, 2 parts of carbon black, Zirconium dioxide-halloysite double network aerogel 10 parts, 2 parts of ammonium polyphosphate, Polypropylene grafted maleic anhydride 0.2 parts, 0.5 parts of tris(2,4-di-tert-butylphenyl)phosphite; Wherein, the length of the carbon fiber is 60nm; and the particle size of the carbon black is 20nm.
[0030] The method for preparing the composite material comprises the following steps: (1) Weigh the components in the appropriate proportions and set aside; (2) Pour polypropylene resin, zirconium dioxide-halloysite double network aerogel, and carbon black into a stirring device and stir evenly to form material group A; (3) Pour ethylene-butene copolymer, polyethylene resin, carbon fiber, ammonium polyphosphate, and polypropylene grafted maleic anhydride into a stirring device and stir evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.
[0031] Among them, the set temperatures of the twin-screw extruder are: section one: 180°C, section two: 185°C, section three: 190°C, section four: 195°C, section five: 185°C, section six: 185°C, section seven: 190°C, section eight: 195°C, section nine: 195°C, and die head: 200°C.
[0032] Wherein, the rotation speed of the twin-screw extruder is 300 rpm.
[0033] A PP black non-absorbent composite material for automobile central control interior parts, comprising the following components in parts by weight: 140 parts of polypropylene resin, 30 parts of ethylene butene copolymer, 20 parts of polyethylene resin, 10 parts of carbon fiber, 3 parts of carbon black, Zirconium dioxide-halloysite double network aerogel 15 parts, 4 parts of ammonium polyphosphate, Polypropylene grafted with maleic anhydride 0.5 parts, 1 part of tris(2,4-di-tert-butylphenyl)phosphite; Among them, the length of the carbon fiber is 90nm; the particle size of the carbon black is 30nm.
[0034] The method for preparing the composite material comprises the following steps: (1) Weigh the components in the appropriate proportions and set aside; (2) Pour polypropylene resin, zirconium dioxide-halloysite double network aerogel, and carbon black into a stirring device and stir evenly to form material group A; (3) Pour ethylene-butene copolymer, polyethylene resin, carbon fiber, ammonium polyphosphate, and polypropylene grafted maleic anhydride into a stirring device and stir evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.
[0035] Furthermore, the set temperatures of the twin-screw extruder are: section one: 200°C, section two: 205°C, section three: 210°C, section four: 215°C, section five: 205°C, section six: 205°C, section seven: 200°C, section eight: 205°C, section nine: 215°C, and die head: 210°C.
[0036] Wherein, the rotation speed of the twin-screw extruder is 500 rpm.
[0037] A PP black non-absorbent composite material for automobile central control interior parts, comprising the following components in parts by weight: 130 parts of polypropylene resin, 25 parts of ethylene butene copolymer, 15 parts of polyethylene resin, 7 parts of carbon fiber, 2.5 parts of carbon black, Zirconium dioxide-halloysite double network aerogel 12 parts, 3 parts of ammonium polyphosphate, Polypropylene grafted maleic anhydride 0.4 parts, 0.8 parts of tris(2,4-di-tert-butylphenyl)phosphite; Among them, the length of the carbon fiber is 80nm; the particle size of the carbon black is 25nm.
[0038] The method for preparing the composite material comprises the following steps: (1) Weigh the components in the appropriate proportions and set aside; (2) Pour polypropylene resin, zirconium dioxide-halloysite double network aerogel, and carbon black into a stirring device and stir evenly to form material group A; (3) Pour ethylene-butene copolymer, polyethylene resin, carbon fiber, ammonium polyphosphate, and polypropylene grafted maleic anhydride into a stirring device and stir evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.
[0039] Furthermore, the set temperatures of the twin-screw extruder are: section one: 190°C, section two: 195°C, section three: 200°C, section four: 205°C, section five: 195°C, section six: 200°C, section seven: 195°C, section eight: 200°C, section nine: 200°C, and die head: 205°C.
[0040] Wherein, the rotation speed of the twin-screw extruder is 400 rpm.
[0041] Comparative Example 1 Comparative Example 1 is consistent with Example 3, except that no zirconium dioxide-halloysite double network aerogel is added in Comparative Example 1.
[0042] Comparative Example 2 Comparative Example 2 is consistent with Example 3, except that no ammonium polyphosphate is added in Comparative Example 2.
[0043] The performance tests were carried out on the composite materials prepared above. The composite materials were first made into standard test specimens according to various national standard test specimens, wherein: the cantilever beam notched impact strength was measured according to the national standard GB / T1843, the tensile strength was measured according to the national standard GB / T1040, and the flexural strength was measured according to the national standard GB / T9341.
[0044] The thermal insulation property was characterized by measuring the thermal conductivity through a thermal conductivity meter; and after the composite material was irradiated with a UV lamp (40W) for 3h (irradiation distance 50mm), the temperature rise value (△T) was measured.
[0045] The blackness is characterized by measuring the L value according to GB / T7921-2008.
[0046] The specific test results are recorded in Table 1.
[0047] Table 1 From the above test data, it can be seen that the composite material prepared by the present invention has good mechanical properties, and its cantilever beam notched impact strength can reach 17.4 kJ·m -2 , the tensile strength can reach 27 MPa, and the flexural strength can reach 36 MPa, which can meet the basic application requirements of automobile central control interior parts; Comparative Example 1 does not contain zirconium dioxide-halloysite double network aerogel, and the composite material is lower than that of Example 3, indicating that zirconium dioxide-halloysite double network aerogel can also improve its sexual properties to a certain extent.
[0048] The flame retardant grades of comparative examples 1-2 are only V-2 and V-1, which are significantly lower than V-0 of example 3, indicating that zirconium dioxide-halloysite double network aerogel and triphenyl phosphate can play the role of flame retardants in the composite material, and in the present invention, the effect of zirconium dioxide-halloysite double network aerogel on flame retardancy is higher than that of triphenyl phosphate; in addition, the joint use of zirconium dioxide-halloysite double network aerogel and ammonium polyphosphate can effectively play a synergistic role to improve the flame retardant properties of the composite material.
[0049] From the test results of thermal conductivity and temperature rise value, it can be seen that the composite material prepared by the present invention has a lower thermal conductivity, indicating that the composite material has excellent thermal insulation performance; at the same time, the temperature rise value data can also support this view. The thermal conductivity of comparative example 1 is much lower than that of example 3, which shows that the zirconium dioxide-halloysite double network aerogel plays a decisive role in the thermal insulation performance in this application.
[0050] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A PP black non-absorbent composite material used for automobile center console interior parts, characterized in that: According to parts by weight, it includes the following components: 120-140 parts of polypropylene resin, 20-30 parts of ethylene butene copolymer, 10-20 parts of polyethylene resin, 5-10 parts of carbon fiber, 1-3 parts of carbon black, 10-15 parts of zirconium dioxide-halloysite double network aerogel, 2-4 parts of ammonium polyphosphate, Polypropylene grafted with maleic anhydride 0.2-0.5 parts, 0.5 to 1 part of tri(2,4-di-tert-butylphenyl)phosphite.
2. The composite material according to claim 1, characterized in that According to parts by weight, it is composed of the following components: 120-140 parts of polypropylene resin, 20-30 parts of ethylene butene copolymer, 10-20 parts of polyethylene resin, 5-10 parts of carbon fiber, 2-3 parts of carbon black, 10-15 parts of zirconium dioxide-halloysite double network aerogel, 2-4 parts of ammonium polyphosphate, Polypropylene grafted with maleic anhydride 0.2-0.5 parts, 0.5 to 1 part of tri(2,4-di-tert-butylphenyl)phosphite.
3. The composite material according to claim 1, characterized in that According to parts by weight, it is composed of the following components: 125-135 parts of polypropylene resin, 24-26 parts of ethylene butene copolymer, 13-17 parts of polyethylene resin, 7-8 parts of carbon fiber, Carbon black 2-2.5 parts, 12-13 parts of zirconium dioxide-halloysite double network aerogel, 3-4 parts of ammonium polyphosphate, Polypropylene grafted with maleic anhydride 0.3-0.4 parts, 0.7 to 0.8 parts of tri(2,4-di-tert-butylphenyl)phosphite.
4. The composite material according to any one of claims 1 to 3, characterized in that: The weight average molecular weight of the polypropylene resin is 50,000 to 60,000, and the melt index is 30 to 50 g / 10 min; the polyethylene resin is a linear polyethylene resin.
5. The composite material according to any one of claims 1 to 3, characterized in that: The length of the carbon fiber is 60-90 nm; the particle size of the carbon black is 20-30 nm.
6. The composite material according to any one of claims 1 to 3, characterized in that: The preparation steps of the zirconium dioxide-halloysite double network aerogel are as follows: (1) dissolving 5 parts of polyethylene glycol in 100 parts of water at 80°C and stirring vigorously for 2 hours; dispersing 10 grams of halloysite nanotubes in 100 parts of water at 40°C and stirring for 10 minutes to obtain a uniform suspension. The polyethylene glycol solution and the halloysite nanotube suspension are mixed, then poured into a container and subjected to ultrasonic dispersion treatment for 20 minutes. Then, 0.5 parts of saturated borax solution are added dropwise to the mixture, and the mixture is stirred continuously until it becomes viscous, and then poured into a mold. The mold is placed in a freezer at -20°C for 24 hours and dried in a vacuum freeze dryer for 8 hours to obtain the first halloysite-polyethylene glycol network aerogel; (2) 10 parts of tetra-tert-butoxy zirconium, 20 parts of anhydrous ethanol and 15 parts of water are added to a reaction container, stirred at 40°C for 15 minutes, and then a concentration of 0.05 mol·L -1 / hydrochloric acid solution, adjust the pH to 2.6, and continue stirring for 20 minutes to obtain ZrO2 sol. Place ZrO2 sol and halloysite-polyethylene glycol first network aerogel in a container in a vacuum environment, immerse the halloysite-polyethylene glycol first network aerogel in ZrO2 sol, and after completely removing air bubbles, add ammonia solution to the sol until the pH is 7.2, and stir the solution evenly for 30 minutes. The sol becomes a wet gel, and then it is immersed in ethanol at room temperature for aging for 24 hours. The aged CO2 supercritical drying tank is supercritically dried to finally obtain zirconium dioxide-halloysite double network aerogel.
7. A method for preparing a PP black non-absorbent composite material for automobile center console interior parts according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Weigh the components in the appropriate proportions and set aside; (2) Pour polypropylene resin, zirconium dioxide-halloysite double network aerogel, and carbon black into a stirring device and stir evenly to form material group A; (3) Pour ethylene-butene copolymer, polyethylene resin, carbon fiber, ammonium polyphosphate, and polypropylene grafted maleic anhydride into a stirring device and stir evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.
8. The method for preparing a composite material according to claim 7, characterized in that: The set temperatures of the twin-screw extruder are: section one: 180-200°C, section two: 185-205°C, section three: 190-210°C, section four: 195-215°C, section five: 185-205°C, section six: 185-205°C, section seven: 190-200°C, section eight: 195-205°C, section nine: 195-215°C, and die head: 200-210°C.
9. The method for preparing a composite material according to claim 7, characterized in that: The rotation speed of the twin-screw extruder is 300-500 rpm.
Citation Information
Patent Citations
A kind of black filled polypropylene composite material and its preparation method and application
CN103467855B
A low heat storage polypropylene composite material for automotive interior parts and its preparation method
CN112011123B